International Provision of Trade Services, Trade, and Fragmentation - Deardorff, Alan V. (World Bank, Washington, DC, 2014)
The author examines the special role that trade liberalization in services industries can play in stimulating trade in both services, and goods. International trade in goods requires inputs from such trade services as transportation, insurance, and finance, for example. Restrictions on services across borders, and within foreign countries add costs, and barriers to international trade. Liberalizing trade in services could also facilitate trade in goods, providing more benefits than one might expect from analysis merely of the services trade. To emphasize the point, the author notes that the benefits for trade are arguably enhanced by the phenomenon of fragmentation. The more that production processes become split across locations, with the fragments tied together, and coordinated by various trade services, the greater the gains from reductions in the costs of services. The incentives for such fragmentation can be greater across countries, than within countries, because of the greater differences in factor prices, and technologies. But the service costs of international fragmentation can also be larger, especially if regulations, and restrictions impede the international provision of services. As a result, trade liberalization in services can stimulate the fragmentation of production of both goods, and services, thus increasing international trade, and the gains from trade even further. Since fragmentation seems to characterize an increasing portion of world specialization, the importance of service liberalization is growing apace.